PERTIMBANGAN ETIKA AGAMA DALAM APLIKASI ILMU (MENDAKWAHKAN ETIKA DALAM ILMU) - Anwar, Muhammad (Jurnal Dakwah Tabligh, 2018)
Ethics is the science of moral philosophy or moral, is nothing other than the science or the "art" of life (the art of living) that teaches how to live a happy life, or how to achieve happiness. Ethics as the art of living ethics as a spiritual treatment. Religion is the most essential human needs that are universal. Therefore, religion is a spiritual awareness in which there is one fact that seemed to have, which is that people always hope for His mercy, guidance of his hands, and caress him, that ontological not be denied, even by people who are most communist though ,